Evaluation of Polyethersulfone‐based Composite for Selective Separation of Cesium from Acidic Media. (23rd May 2016) - Park, Jai Il; Kim, Jung Suk; Kim, Young Bok; Kwon, Hye Jung; Park, Yong Joon
Abstract : Abstract : This article describes the performance of inorganic–organic ion exchanger for the separation of cesium ion from acidic media. The composite consisted of ammonium molybdophosphate and polyethersulfone as a functional adsorbent and a polymeric support, respectively. The physicochemical properties of the polymer composite were examined using different techniques including thermogravimetric analysis, scanning electron/optical microscopy, and infrared spectrometry. Cesium sorption capacity of the composite was evaluated through batch studies under various conditions. The dynamic sorption and recovery were also studied by performing column experiments. In addition, we demonstrated the possible use of the synthesized granule for the selective recovery of radioactive cesium in a post‐irradiated nuclear material solution containing multiple fission products.